Alcohol and Indian porphyrics. Issue 791 (September 1991) - Saksena, H. C.; Panwar, R. B.; Rajvanshi, P.; Sabir, M.; Suri, M.
Abstract : The role of alcohol as the precipitating factor in the induction of acute attacks of acute intermittent porphyria was studied in an Indian population. Thirty-four teetotal patients with acute intermittent porphyria, in remission, were given 60 ml of 30% ethanol. Except for two patients, all had negative Watson-Schwartz tests prior to the alcohol. Within 24 hours, the Watson-Schwartz test became positive in 16 of these 32 patients (50%). In 8 out of the 34 patients (23.5%) a clinical attack was precipitated, including both patients who had a positive Watson-Schwartz test prior to the alcohol. It was concluded that alcohol does precipitate an acute attack in a significant percentage of patients of Indian origin with acute intermittent porphyria. Patients already excreting porphobilinogen are at a greater risk of developing an acute attack on alcohol ingestion. This study is the first from India and probably first of its kind to be reported from any country.